2014
DOI: 10.2105/ajph.2014.301946
|View full text |Cite
|
Sign up to set email alerts
|

The Sexual Victimization of Men in America: New Data Challenge Old Assumptions

Abstract: We assessed 12-month prevalence and incidence data on sexual victimization in 5 federal surveys that the Bureau of Justice Statistics, the Centers for Disease Control and Prevention, and the Federal Bureau of Investigation conducted independently in 2010 through 2012. We used these data to examine the prevailing assumption that men rarely experience sexual victimization. We concluded that federal surveys detect a high prevalence of sexual victimization among men-in many circumstances similar to the prevalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
145
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(155 citation statements)
references
References 21 publications
8
145
2
Order By: Relevance
“…In fact, recent studies from the US have reported male victimization rates similar to those for women (Stemple & Meyer, 2014;Turchik, 2012). Respondents in the present study did not deny the possibility of male victimization.…”
Section: Discussioncontrasting
confidence: 52%
“…In fact, recent studies from the US have reported male victimization rates similar to those for women (Stemple & Meyer, 2014;Turchik, 2012). Respondents in the present study did not deny the possibility of male victimization.…”
Section: Discussioncontrasting
confidence: 52%
“…Service providers and educators are encouraged to address sexual violence risk among all drug users and are cautioned against gendered interpretations that rely exclusively on a female victim/male perpetrator paradigm. Recent research has found a high prevalence of sexual violence victimization among young adult males in the United States (Snipes et al, 2014; Stemple & Meyer, 2014) further supporting our emphasis on a drug using context and culture.…”
Section: Discussionmentioning
confidence: 69%
“…It is estimated that 1 in 5 women are raped during their lifetime and, although less frequently reported, males also experience sexual victimization at disturbing rates (Centers for Disease Control and Prevention [CDC], 2014, Stemple & Meyer, 2014). In addition to rape, the term sexual violence as used here encompasses other sexual violations, including sexual harassment, coercion (e.g., pressuring, verbal threats), and nonconsensual touching (Basile & Saltzman, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Research supports a number of risk factors related primarily to IPV victimization among nationally representative samples of men and women who use drugs, including younger age, lower income, depression, poor sexual relationship power, poor social support, and sexual risk-taking behaviors (Campbell et al 2009, 2012; Dunkle et al 2004; Gage and Hutchinson 2006; Gilbert et al 2012; Jewkes et al 2010; Pulerwitz, Gortmaker, and DeJong 2000; Teitelman et al 2008). Despite the high prevalence of IPV victimization among men (Black et al 2011), there is limited literature on risk factors for such experiences (Carney, Buttell, and Dutton 2007; Dutton and Goodman 2005; Dutton and Nicholls 2005; Enander 2011; Hines and Douglas 2010; Stemple and Meyer 2014). Specifically, the IPV literature has been largely guided by male-perpetrator/female-victim models (Stith et al 2004).…”
Section: Introductionmentioning
confidence: 99%